Cisza i światło jako środki wyrażania "sacrum" (na przykładzie "Pieśni o Bogu ukrytym" Karola Wojtyły i tomiku "Postać w bieli" Czesława Sobkowiaka ) = Silence and light as means for expressing "sacrum" (based on the "Song of the Hidden God" by Karol Wojtyla and the volu me "The person in white" by Czeslaw Sobkowiak) - Krysińska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Silence and light are multi-faceted phenomena. In the "Song of the Hidden God" by Karol Wojtyla and the volume "The person in white" by Czeslaw Sobkowiak they have a special metaphysical significance. The symbolism of these phenomena penetrates Wojtyla`s poem and constitutes its religious meanings.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; Sobkowiak, Czesław (1950 -) - twórczość; poezja polska - 20 w.; polish poetry; silence; light; cisza; światło